2011
DOI: 10.1002/pssb.201100179
|View full text |Cite
|
Sign up to set email alerts
|

CVD growth and processing of graphene for electronic applications

Abstract: The remarkable properties of graphene have potential for numerous applications; however, their exploitation depends on its reliable production. The chemical vapour deposition (CVD) growth of graphene on metal surfaces has become one of the most promising strategies for the production of high quality graphene in a scaleable manner. Here, we discuss graphene growth on nickel (Ni) and copper (Cu) directly from both gaseous hydrocarbons and solid carbon precursors. Further, we discuss in detail the transfer of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Recent research has shown that the unique physical, chemical and electronic properties of graphene may be exploited in a wide range of applications; namely sensing, 1,2 electronics 3,4 and energy. 5,6 In particular, energy conversion and storage technologies that take advantage of graphene's excellent mechanical strength, chemical stability and high surface area may be developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that the unique physical, chemical and electronic properties of graphene may be exploited in a wide range of applications; namely sensing, 1,2 electronics 3,4 and energy. 5,6 In particular, energy conversion and storage technologies that take advantage of graphene's excellent mechanical strength, chemical stability and high surface area may be developed.…”
mentioning
confidence: 99%
“…In brief, GO powder was synthesised by a modified Hummers and Offeman method 32 to produce the starting material. Gram scale quantities of this material were placed in a chamber downstream from a radical plasma generator at 1000 W with a gas flow of 100 sccm of a 1 : 1 mixture of H 2 and NH 3 . No direct heating of the GO took place and the lack of applied bias in the vicinity of the sample minimised kinetic damage from accelerated ions.…”
mentioning
confidence: 99%
“…Graphene was produced using chemical vapor deposition (CVD) on copper (Cu) foils as described in detail in our previous work. 26 The graphene was then transferred onto the pre-patterned substrate, directly after removing the native oxide layer from the exposed silicon surface with HF, in order to form a direct contact between the graphene and the silicon. One end of the graphene lies on the n-Si surface without touching the metal electrode deposited on the n-Si, and the other end sits on the gold pad on the SiO 2 layer which insulates a direct contact between the metal electrode and the Si substrate.…”
mentioning
confidence: 99%
“…In the uncovered catalyst areas graphene growth was observed [21]. The quality of the produced graphene features was analysed using optical microscopy, SEM and Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%